Lateral Compartmentalization of T Cell Receptor Versus CD45 by Galectin-N-Glycan Binding and Microfilaments Coordinate Basal and Activation Signaling - I‐Ju Chen; Hung-Lin Chen; Michael A. Demetriou (2007)
Lateral compartmentalization of membrane proteins into microdomains regulates signal transduction; however, structural determinants are incompletely understood. Membrane glycoproteins bind galectins in proportion to the number (i.e. NX(S/T) sites) and degree of GlcNAc branching within attached N-glycans, forming a molecular lattice that negatively regulates T cell function and autoimmunity. We find that in resting T cells, partition of CD45 inside and T cell receptor (TCR)/CD4-Lck/Zap-70 outside microdomains is positively and negatively regulated by the galectin lattice and actin cytoskeleton, respectively. In the absence of TCR ligands, the galectin lattice counteracts F-actin to retain CD45 in microdomains while concurrently blocking TCR/CD4-Lck/Zap-70 partition to microdomains by preventing a conformational change in the TCR that recruits Nck/Wiscott Aldrich Syndrome (WASp)/SLP76/F-actin/CD4 to TCR. The counterbalancing activities of the galectin lattice and actin cytoskeleton negatively and positively regulate Lck activity in resting cells and CD45 versus TCR clustering and signaling at the early immune synapse, respectively. Microdomain-localized CD45 inactivates Lck and inhibits TCR signaling at the early immune synapse. Thus, the galectin lattice and actin cytoskeleton interact on opposing sides of the plasma membrane to control microdomain structure and function, coupling basal growth signaling with thresholds to activation.